2007
DOI: 10.1016/j.technovation.2007.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Industry work experience and inventive capacity of South African academic researchers

Abstract: The inventive capacity of South African universities and researchers is investigated through analysis of university patent applications. Patent applications to the South African Patent office from 1996 to 2006 are used as an indicator of inventive capacity.The investigation determines, for the first time, patenting activities of local universities at the South African Patent Office for the past 10 years and it identifies the performance of faculties and departments. We suggest that patent analysis of local pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 32 publications
(25 reference statements)
2
24
0
Order By: Relevance
“…Although some of the studies view IAR as a more effective mechanism to protect SMEs' innovative inventions, others studies stress that the practice of FAR is also another effective way of protecting innovative inventions from rival firms [5,24,25]. For instance, SMEs gain the advantages of the patent strategy in situations where the SMEs perceive the potential benefits of their patent enrollments as any potential acquisition or enhancement of their market positions.…”
Section: Appropriability Regime Of Smesmentioning
confidence: 99%
“…Although some of the studies view IAR as a more effective mechanism to protect SMEs' innovative inventions, others studies stress that the practice of FAR is also another effective way of protecting innovative inventions from rival firms [5,24,25]. For instance, SMEs gain the advantages of the patent strategy in situations where the SMEs perceive the potential benefits of their patent enrollments as any potential acquisition or enhancement of their market positions.…”
Section: Appropriability Regime Of Smesmentioning
confidence: 99%
“…The inventiveness effect may thus be increasing the network of collaborators and this has the potential to promote and facilitate the spill over or transfer of knowledge that can leverage the publication capacity. In a recent work, Lubango and Pouris [24] found that professors with previous industry working experience were more inventive than those who do not have such experience in South African higher education institutions. This observation was in line with those of Bozeman and Corley [19,24,25], which showed that professors who have previous industry working experience have broader social networks, broader social capital, and stronger ties with industry and funding bodies than those whose entire career has been spent in a university.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent work, Lubango and Pouris [24] found that professors with previous industry working experience were more inventive than those who do not have such experience in South African higher education institutions. This observation was in line with those of Bozeman and Corley [19,24,25], which showed that professors who have previous industry working experience have broader social networks, broader social capital, and stronger ties with industry and funding bodies than those whose entire career has been spent in a university. It is thus believed that previous industry working experience not only increases technical capital but also increases social networks and social capital of a researcher which can be translated in research outputs of higher national and international standards.…”
Section: Resultsmentioning
confidence: 99%
“…The first paper [26] reported on an investigation into the effects of employing researchers with previous industry work experience. The research found that such employment is an effective mechanism for increasing the core skills of technological innovation in mainstream universities, which ultimately translates into higher inventive capacity.…”
Section: Resultsmentioning
confidence: 99%